Mediation effect of peripheral blood inflammatory factors in the association between severity of nonlactating mastitis and glycemic abnormalities: Mediation of Inflammatory Factors in Mastitis and Glycemic Abnormalities - Qi, Dianchun; Lin, Yiqi; Zhang, Jiaxin; Wang, Yiping (Journal of Medical Biochemistry, 2024)
Background: The association between severity of non-lactating mastitis and glycemic abnormalities was analyzed to investigate the mediating role of peripheral inflammatory factor levels in the association. Methods: A total of 337 cases were included in this study, including 195 cases in the control group and 142 cases in the case group. Multifactorial logistic regression was used to analyze the associations between the severity of NLM and glycemic abnormality and peripheral inflammatory factors, and a mediation model was used to explore the mediating roles of the levels of hs-CRP, WBC, and IL-6 in the associations between the two. Results: The inflammatory factors IL-6, WBC, and hs-CRP had mediating effects, with effect values of 0.009 (0.003-0.038), 0.006(0.001-0.047), and 0.007(0.001-0.051), and mediating effect percentages of 2.38%, 2.12%, and 2.24%, respectively. Conclusion: NLM severity and glycemic abnormalities were positively correlated with peripheral inflammatory factors, and peripheral inflammatory factors played a partial mediating role in the association.
Keywords: Non- lactation mastitis; Inflammatory cytokines; Glucose abnormality; Mediating effect